Legal Principle Between Concept and Content - Latyshev, Oleg Yurievich; Skorobogatov, Andrei Valerievich; Krasnov, Alexander Valerievich (Faculty of Law, Universitas Negeri Semarang, 2020)
The article is devoted to the study of the legal nature of legal principles. The purpose of the article is a comprehensive study of the legal and social aspects of the essence and content of the legal principle as a philosophical and legal category. The methodological basis of the article is an integrative approach to the study of legal reality, which allowed us to combine general scientific and private scientific methods developed in various scientific paradigms and study the principles of law not only ontologically, but also epistemologically and axiologically, taking into account the phenomenological and communicative aspects of their content, development, and functioning. This paper emphasized that the study of legal principles not only in the legal, but also in the general social context allows us to conclude that this category is fundamental in the construction of legal reality cognitively, functionally, and normatively. The legal principle is the conventional result of legal communication. As a fundamental category of legal reality, the principle determines the nature of its analysis, interpretation, and evaluation. The scientific novelty of the article is determined by the specifics of the research methodology and the findings obtained, which allow us to determine the fundamental role of the legal principle at all levels of legal reality. The practical significance of the article lies in the ability to use the findings in the study of other aspects of the development and functioning of legal reality, as well as in generating forecasts for the development of the national legal system.